2007
DOI: 10.1002/jnr.21250
|View full text |Cite
|
Sign up to set email alerts
|

Cardiovascular effects of noradrenaline microinjection in the bed nucleus of the stria terminalis of the rat brain

Abstract: The bed nucleus of the stria terminalis (BST) is a limbic structure involved in regulating the hypothalamic-pituitary-adrenal axis as well as in central cardiovascular control. We report here on cardiovascular effects caused by microinjection of noradrenaline (NA) in the BST of the rat brain and the peripheral mechanisms involved in their mediation. Injection of NA (3, 7, 10, 15, 30, or 45 nmol in 100 nl) in the BST of unanesthetized rats caused long-lasting dose-related pressor and bradycardiac responses. No … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
40
0
4

Year Published

2007
2007
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(45 citation statements)
references
References 40 publications
1
40
0
4
Order By: Relevance
“…PVN paraventricular nucleus of hypothalamus, BNST bed nucleus of stria terminalis, dmPAG dorsomedial periaqueductal gray, PL and IL prelimbic and infralimbic prefrontal cortex, MeA medial amygdaloid nucleus, DBB diagonal band of Broca, dlPAG dorsolateral periaqueductal gray, and Cg1 cingulate cortex area 1 * Different from vehicle-treated group (aCSF) group, P \ 0.0001 # Different from NA-treated (NA) group, P \ 0.0001 structures are activated after administration of NA into the LSA. All these structures are able to cause vasopressin release to periphery after stimulation Crestani et al 2007;Fernandes et al 2003;Fortaleza et al 2011;Pelosi and Correa 2005). In contrast, no changes in the pattern of c-Fos expression were found in the diagonal band of Broca (DBB), cingulate cortex 1 (Cg1), and dorsolateral periaqueductal gray (dlPAG).…”
Section: Discussionmentioning
confidence: 99%
“…PVN paraventricular nucleus of hypothalamus, BNST bed nucleus of stria terminalis, dmPAG dorsomedial periaqueductal gray, PL and IL prelimbic and infralimbic prefrontal cortex, MeA medial amygdaloid nucleus, DBB diagonal band of Broca, dlPAG dorsolateral periaqueductal gray, and Cg1 cingulate cortex area 1 * Different from vehicle-treated group (aCSF) group, P \ 0.0001 # Different from NA-treated (NA) group, P \ 0.0001 structures are activated after administration of NA into the LSA. All these structures are able to cause vasopressin release to periphery after stimulation Crestani et al 2007;Fernandes et al 2003;Fortaleza et al 2011;Pelosi and Correa 2005). In contrast, no changes in the pattern of c-Fos expression were found in the diagonal band of Broca (DBB), cingulate cortex 1 (Cg1), and dorsolateral periaqueductal gray (dlPAG).…”
Section: Discussionmentioning
confidence: 99%
“…The c-Fos induction in the rostral BNST region correlated strongly with anxietylike responses, whereas c-Fos induction in the caudal BNST correlated with panic-like cardiovascular responses. Although other studies have demonstrated that the BNST regulates anxiety-like behavior (Sajdyk et al, 2007) and autonomic activity (Crestani et al, 2007), the BNST's role may depend on the context. In the present article, a subsequent experiment (ie experiment 3) demonstrated that inactivation of the rostro-caudal BNST region (see Figure 4) with acute muscimol injections selectively blocked the anxiogenic effects of the lactate + L-AG infusions without affecting the cardiorespiratory activation, providing strong support for the hypothesis that the BNST selectively regulates anxiety behavior, but not panic-like cardiorespiratory responses in the panic model presented here (see Figure 5a for a hypothetical model).…”
Section: Pathways For Lactate-induced Panic-like Responsesmentioning
confidence: 90%
“…O pentolínio causou potencialização semelhante em respostas pressoras causadas pela microinjeção de NA em outras regiões do cérebro, sugerindo o envolvimento de uma mediação humoral. Outros estudos do nosso grupo mostraram que o aumento da pressão arterial e queda na frequência cardíaca causado pela microinjeção de NA em diversas regiões do cérebro foi mediado por liberação de vasopressina (CORREA et al, 1985;FERNANDES et al, 2003;PELOSI e CORREA, 2005;SCOPINHO et al, 2006;CRESTANI et al, 2007;PELOSI et al, 2008;BUSNARDO et al, 2009a).…”
Section: Discussionunclassified
“…Além disso, existe uma via indireta da amígdala para o núcleo leito da estria terminal (NLET) e da área pré-óptica que conecta-se com a amígdala para o núcleo paraventricular (SAWCHENKO e SWANSON, 1983;MCDONALD, 1988). O NLET é um componente heterogêneo funcional da amígdala estendida que tem sido implicado na modulação das respostas cardiovasculares (CRESTANI et al, 2007). Administração de NA no NLET causa resposta pressora e bradicardia que dependem da liberação de vasopressina pelo NPV (CRESTANI, BUSNARDO et al, 2009).…”
Section: Discussionunclassified
See 1 more Smart Citation